Fluvial sediment yield in the Sungai Behar peat swamp forest: a summary of source, concentration and transportation / Mohd Ekhwan Toriman - Toriman, Mohd Ekhwan (2006)
In a natural environment, sediments in river play an important role in elemental cycling in the aquatic environment. Sediments are responsible for transporting a significant proportion of many nutrients and contaminants. They also mediate their uptake, storage, release and transfer between environmental compartments. Most sediment in surface waters derives from surface erosion and comprises a mineral component, arising from the erosion of bedrock, and an organic component arising during soil-forming processes. However, over sediment flux may result changes on water quality and flow regimes. This paper addresses the impacts of land development on sediment yield in the Sungai Bebar Peat Swamp Forest (SBPSF). Hydrometeorological conditions and sediment yield produced from Sungai Bebar catchment were investigated in the month of February and April 2005. Mean annual rainfall and Run off were calculated at 2244 111m and 1367 mm, respectively. These results are within the predicted by HP No 12 where PE IS between 1000-1500 mm year'l. Meanwhile, hydrometeorological and flow conditions playa crucial role in sediment transport within the Sungai Bebar/Serai system. Sungai Serai contributes 81.2 percent of total sediment load to the Sungai Bebar. All together, the total monthly sediment yield for Sungai Bebar is 3.06 kg/km2 or 36.7 kg/ km2/yr-1. The volume is lower compared with Sungai Serai which shows higher sediment yield as estimated at 13.2 kg/km2 or 158.4 kg/km2/yr-1. This study suggests both long and short terms management and conservation approaches 10 minimize the impacts.